Biological properties of the benzodiazepine amidine derivative L-740,093, a cholecystokinin-B/gastrin receptor antagonist with high affinity in vitro and high potency in vivo. - Patel, S; Smith, A; Chapman, K; Fletcher, A; Kemp, J; Marshall, G; Hargreaves, R; Ryecroft, W; Iversen, L; Iversen, S (1994)
A novel series of 5-amino-1,4-benzodiazepin-2-one derivatives (amidines), which contain a cationic solubilizing group and which are antagonists for the cholecystokinin (CCK)-B receptor, have been identified. Optimization of this series led to the identification of an azabicyclononane amidine, L-740,093 [N-[(3R)-5-(3-azabicyclo[3.2.2]nonan-3-yl)-2,3-dihydro-1-methyl-2- oxo- 1H-1,4-benzodiazepin-3-yl]-N'-(3-methylphenyl)urea], that bound with high affinity of CCK-B receptors from guinea pig cerebral cortex (IC50 of 0.1 nM) and had a CCK-B/CCK-A receptor selectivity of 16,000. In comparison, L-365,260 had 85-fold lower affinity (8.5 nM) and was only 87-fold selective for CCK-B over CCK-A receptors. L-740,093 bound with high affinity to guinea pig gastrin receptors in vitro (IC50 of 0.04 nM). Electrophysiological studies on slices of rat ventromedial hypothalamic nucleus showed that L-740,093 produced rightward shifts of the concentration-response curve for the CCK-B receptor agonist pentagastrin (Kb of 0.06 nM). L-740,093 blocked pentagastrin-induced gastric acid secretion in anesthetized rats with a 50% inhibitory dose of 0.01 mg/kg, intraperitoneally, showing 100-fold greater activity, compared with L-365,260 (50% inhibitory dose of 1 mg/kg, intraperitoneally). An ex vivo binding assay in mice was used to investigate the interaction of L-740,093 with central CCK binding sites. After intravenous administration, L-740,093 inhibited ex vivo binding dose dependently, with a 50% effective dose of 0.2 mg/kg. These studies demonstrate that L-740,093 is the most potent and selective CCK-B antagonist yet described and that it has excellent central nervous system penetration.